Grain mineral composition based-comparison of Miracle wheat (T. turgidum convar. compositum) with some landraces and modern wheat varieties - Atar, Bekir (Progress in Nutrition, 2019)
Wheat landraces still maintain their value because of their importance in terms of genetic resource, attaining old tastes and natural nutrient contents as well as their use as a breeding material. Of the ancient wheats, miracle wheat is one of those about which speculations have been made at different points of time over the last few centuries. These speculations have been mainly based on yield. It is clear that, in its current form, it cannot be an alternative to modern wheats in terms of yield. However, as a breeding material, its characteristics need to be studied. In the study, protein contents of the varieties ranged from 9.6% to 18.3%. The lowest protein content was found in Zerun and the highest in Einkorn. Phosphorus (P), potassium (K), magnesium (Mg), calcium (Ca), iron (Fe), copper (Cu), manganese (Mn) and zinc (Zn) concentrations of the varieties ranged between 2.6 and 4.6, 3.3 and 5.3, 1.5 and 1.9, 0.28 and 0.44 g kg-1, 18.1 and 42.3, 4.3 and 8.8, 27.5 and 47.2, and 24.3 and 38.1 mg kg-1, respectively. The highest P, K, Mg and Ca contents were found in Miracle wheat. Besides, miracle wheat was in the group with the highest values in terms of Fe, Cu, Mn, and Zn. In general, the varieties with the lowest mineral contents were Zerun and Emmer.